2009
DOI: 10.1197/jamia.m3169
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Use of a Personal Health Record in a Managed Care Organization

Abstract: Differences in education, income, and Internet access did not account for the disparities in PHR registration by race. In the short-term, attempts to improve patient access to health care with PHRs may not ameliorate prevailing disparities between African Americans and whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
164
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(182 citation statements)
references
References 19 publications
13
164
3
2
Order By: Relevance
“…A subsequent study from Kaiser Permanente-Georgia showed higher enrollment in the patient portal among white patients. 3 Finally, a more recent study from Kaiser Permanente-Northern California of patients with diabetes showed persistence of racial and ethnic disparities in enrollment even after adjustment for health literacy. 5 The only study of a patient population outside of Kaiser Permanente examined enrollment in a patient portal among patients at an academic practice in Boston.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A subsequent study from Kaiser Permanente-Georgia showed higher enrollment in the patient portal among white patients. 3 Finally, a more recent study from Kaiser Permanente-Northern California of patients with diabetes showed persistence of racial and ethnic disparities in enrollment even after adjustment for health literacy. 5 The only study of a patient population outside of Kaiser Permanente examined enrollment in a patient portal among patients at an academic practice in Boston.…”
Section: Discussionmentioning
confidence: 97%
“…Although preliminary results indicate possible disparities in enrollment by a variety of factors such as race/ethnicity, these studies did not examine whether this was due to differences in patients' ability to access the internet, differential offering of the portal to patients by physicians, or rates of acceptance by patients after being offered access. [3][4][5][6] Low rates of enrollment could be due to a variety of factors including patient level factors such as distrust in electronic communications or barriers to use (e.g., computer literacy). In addition, it is unclear whether there are differences in how often patients use patient portals after enrollment or their type of use (e.g., soliciting advice, requesting medication refills).…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Among portal registrants at the Cleveland Clinic, whites were more likely than blacks to use the account after registering for it. 15 A cohort study at Kaiser Permanente Georgia found that portal registration was more likely among whites, those with Internet access at baseline, and those with more education.…”
Section: Introductionmentioning
confidence: 99%
“…A strength of this study is its focus on a linguistically diverse patient population with multiple chronic conditions receiving care in an integrated group practice setting. Research has shown that minorities in general are less likely to use online health-related patient SMRs or portals, [12][13][14] and our results suggest that speaking a non-English language is associated with low use of remote refill systems, including the Internet.…”
Section: Discussionmentioning
confidence: 52%
“…11 African Americans and Latinos are less likely to use an online SMR system that has options to request medication refills. [12][13][14] In view of the lack of reliable data on patient language use in most health care systems, and the enormous challenges of conducting cross-cultural and multi-lingual research, to our knowledge, there are no studies examining the use of the medication refill functionality of SMRs by linguistically diverse populations. This study addresses this gap by investigating the use of Internet and telephone medication refill systems integrated within an SMR among an ethnically diverse sample of insured patients with chronic illnesses, and investigates differences in use between patients with limited English proficiency (LEP) and English-proficient (EP) patients.…”
Section: Introductionmentioning
confidence: 99%